A Comprehensive Bibliometric Analysis of the Sport of Squash (1973–2024): Progress, Collaboration, Findings, and Thematic Evolution - Ruizhi Liu; Miran Kondrič; Jihong Wang (Sports)
Squash, which originated in the early 19th century, was officially incorporated into the 2028 Los Angeles Olympic Games by the International Olympic Committee in 2023. This inclusion marks a significant milestone, highlighting its growing international recognition and potential for global development. However, squash has historically been underrepresented in academic research compared to other popular sports, with studies being scattered and relatively underdeveloped. To systematically evaluate the current state of squash research and foster academic development in the field, this study employs a combination of bibliometric and qualitative analyses, aiming to provide a comprehensive overview of squash research in terms of research progress, collaboration networks, key findings, and thematic evolution. Drawing on Web of Science, Scopus, and PubMed data, the analysis covers 206 publications from 36 countries spanning from 1973 to 2024. Network analysis based on co-authorship frequency and geographic clustering identifies the UK and Australia as leading contributors, with extensive collaboration among institutions and authors. Performance analysis (tactical and technical modeling), physiological profiling (energy demands), and medical studies (injury epidemiology) emerged as the three core research areas. The study reveals a shift in research focus from safety and physiological characteristics to performance enhancement, which is driven by technological innovation. Future research should prioritize underdeveloped areas such as youth development, psychology, and nutrition while integrating diverse participant groups (e.g., female athletes, recreational players) and advanced technologies.